SISTEM TANGGUNG RENTENG DALAM PEMBERIAN KREDIT MODAL USAHA PNM MEKAAR - Nadila Annisa; Adlin Budhiawan (JURNAL ILMIAH LIVING LAW, 2023)
According to the study's findings, the debtor is also an individual guarantee under the shared responsibility system, and the Civil Code's articles 1278 and 1280 provide legal protection for creditors. This study aims to shed light on how to implement the millennial economic strategy in a way that benefits both transaction actors and those who carry out transactions. Normative juridical research examines the doctrines or principles of the Science of Law. The quantity of tests in this review were 6 individuals. The study's findings demonstrate that debtors are also individuals under the joint responsibility system. The group is obligated to pay the debtors for their services, but the large number of installments causes members to feel resentment. This is because group members are also expected to pay back their loans. The credit disbursement processing does not begin as a result of this default's occurrence, which has consequences for the group it belongs to. This indicates that it is extremely challenging for the concerned group as well as other groups.